2024
DOI: 10.3389/fneur.2024.1379243
|View full text |Cite
|
Sign up to set email alerts
|

Gait-modifying effects of augmented-reality cueing in people with Parkinson’s disease

Eva M. Hoogendoorn,
Daphne J. Geerse,
Annejet T. van Dam
et al.

Abstract: IntroductionExternal cueing can improve gait in people with Parkinson’s disease (PD), but there is a need for wearable, personalized and flexible cueing techniques that can exploit the power of action-relevant visual cues. Augmented Reality (AR) involving headsets or glasses represents a promising technology in those regards. This study examines the gait-modifying effects of real-world and AR cueing in people with PD.Methods21 people with PD performed walking tasks augmented with either real-world or AR cues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The descriptive plot (Figure 2) illustrated that both methods provided equivalent results. In addition, JAMOVI has the TOSTER plugin; 47,48 it provides a detailed comparison between paired groups. Figure 3 showed that the reference method and the proposed method provided close osmium concentration.…”
Section: ■ Comparing Two Dependent Groupsmentioning
confidence: 99%
“…The descriptive plot (Figure 2) illustrated that both methods provided equivalent results. In addition, JAMOVI has the TOSTER plugin; 47,48 it provides a detailed comparison between paired groups. Figure 3 showed that the reference method and the proposed method provided close osmium concentration.…”
Section: ■ Comparing Two Dependent Groupsmentioning
confidence: 99%
“…While the exact neural mechanisms behind cueing are not fully understood, it is generally agreed that cueing shifts locomotor control from automatic processes to more goal-directed actions [ 51 , 52 ]. This shift involves increased activation of the prefrontal cortex (PFC) and other regions associated with attention and sensorimotor integration [ 53 ].…”
Section: Study Of the Literaturementioning
confidence: 99%